Modifications to rhesus macaque TCR constant regions improve TCR cell surface expression. - Lori V Coren; Matthew T Trivett; Jorden L Welker; James A Thomas; Robert J Gorelick; Emek Kose; Taina T Immonen; Kelli Czarra; Christine M Fennessey; Charles M Trubey; Jeffrey D Lifson; Adrienne E Swanstrom (PLoS ONE)
T cell immunotherapy success is dependent on effective levels of antigen receptor expressed at the surface of engineered cells. Efforts to optimize surface expression in T cell receptor (TCR)-based therapeutic approaches include optimization of cellular engineering methods and coding sequences, and reducing the likelihood of exogenous TCR α and β chains mispairing with the endogenous TCR chains. Approaches to promote correct human TCR chain pairing include constant region mutations to create an additional disulfide bond between the two chains, full murinization of the constant region of the TCR α and β sequences, and a minimal set of murine mutations to the TCR α and β constant regions. Preclinical animal models are valuable tools to optimize engineering designs and methods, and to evaluate the potential for off-target tissue injury. To further develop rhesus macaque models for TCR based cellular immunotherapy, we tested methods for improving cell surface expression of rhesus macaque TCR in rhesus macaque primary cells by generating five alternative TCRαβ constant region constructs in the context of a SIV Gag-specific TCR: 1. human codon optimized rhesus macaque (RH); 2. RH TCR with an additional disulfide linkage; 3. rhesus macaque constant sequences with minimal murine amino acid substitutions; 4. murinized constant sequences; and 5. murinized constant sequences with a portion of the exposed FG loop in the β constant sequence replaced with rhesus macaque sequence to reduce potential immunogencity. Murinization or mutation of a minimal set of amino acids to the corresponding murine sequence of the constant region resulted in the greatest increase in rhesus macaque TCR surface expression relative to wild type. All novel TCR constructs retained the ability to induce production of cytokines in response to cognate peptide antigen specific stimulation. This work can inform the design of TCRs selected for use in rhesus macaque models of TCR-based cellular immunotherapy.